Foreign ownership in Finland: Boosting firm performance and changing corporate governance - Pekka Ylä-Anttila; Jyrki Ali-Yrkkö; Martti Nyberg (The Research Institute of the Finnish Economy (ETLA), 2004)
During the last 10 to 15 years the ownership structure of Finnish business has changed in Finland perhaps more profoundly than in any other European country. Since the early 1990s both portfolio investment by foreigners and inward foreign direct investment (FDI) have grown rapidly. Helsinki Stock Exchange has become one of the most internationalised stock exchanges in the world. Cross-border mergers and acquisitions have increased too. In the 1990s, the number of inward cross-border deals in relation to DDP was the second highest in Finland among EU countries. However, the stock of inward FDI in relation to GDP in Finland is still slightly below the EU average. Growing inflows of capital and increasing foreign ownership have, to a large extent, had a positive impact on economic efficiency. The rate of return on capital has increased more rapidly in companies with high foreign ownership. The same applies to labour productivity. It is not clear, however, how foreign ownership has affected Finnish companies' R&D and their long-run growth prospects. Informal evidence seems to indicate that even in this respect the impacts of foreign ownership have been positive. Increasing foreign ownership and globalization of business have triggered major changes in corporate governance towards the US model. – FDI ; foreign ownership ; economic growth ; corporate governance – – Yritysten omistusrakenne Suomessa on muuttunut viimeisten 10-15 aikana dramaattisesti. Ulkomaisten omistajien osuus pörssiyhtiöissä on kasvanut ja myös suorat sijoitukset Suomeen ovat lisääntyneet. Usein ulkomaisten yrityskauppojen kohteena ovat olleet teknologiaintensiiviset pk-yritykset. Ulkomaalaisten Suomesta ostamien yritysten lukumäärä suhteessa talouden kokoon on Suomessa ollut Euroopan korkeimpia. Suomeen tulleiden investointien kanta suhteessa BKT:een on kuitenkin vielä jonkin verran alle EU:n keskiarvon. Ulkomaisten investointien vaikutukset kotimaan talouteen ovat olleet pääosin myönteisiä. Yritysten tehokkuus on kasvanut: pääoman tuottoaste ja työn tuottavuus ovat suurempia yrityksissä, joissa on merkittävä ulkomaalaisomistus. Myös vaikutukset teknologiseen kehitykseen ovat tapaustutkimusten perusteella positiivisia. Olemassa olevan tiedon perusteella ei kuitenkaan voida tehdä varmoja päätelmiä ulkomaalaisomistuksen lisääntymisen pitkän aikavälin kasvuvaikutuksista. Ulkomainen omistus on muuttanut merkittävästi yritysten johtamis- ja valvontajärjestelmiä yhdysvaltalaisen mallin ja omistajavetoisen johtamisjärjestelmän suuntaa.
Keywords: 330; Suorat sijoitukset; ulkomainen omistus; taloudellinen kasvu; johtamis- ja valvontajärjestelmät.; Multinationales Unternehmen; Direktinvestition; Eigentümerstruktur; Unternehmensentwicklung; Corporate Governance; Finnland